2007
DOI: 10.1002/j.2055-2335.2007.tb00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface Contamination from Cytotoxic Chemotherapy Following Preparation and Administration

Abstract: Background: Surface contamination with cytotoxic drug residue is a potential occupational health hazard to staff working in cytotoxic compounding areas and oncology wards. Aim: To identify surfaces contaminated with cytotoxic drug residue and to indicate the risk of exposure to health workers handling cytotoxic drug residue. Method: Wipe sampling was used to investigate surface contamination and occupational skin exposure to the marker cytotoxic drugs, fluorouracil (5-FU) and gemcitabine (GEM), in the pharmacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…This has been supported by the results of many other studies [19,21,22,27,40,41], and is insofar critical as gloves are often not worn in areas where no contamination is expected [42]. Nevertheless, the present findings generally range in lower magnitudes than results from older studies [13,33,43,44] and also from more recent international studies [19,28,31,41,[45][46][47], indicating country-specific levels of contamination and pointing out the constant improvements in occupational hygiene practice in the participating pharmacies. The continuous improvement is likely to have benefitted from repeated and long-term monitoring.…”
Section: Overall Resultssupporting
confidence: 91%
“…This has been supported by the results of many other studies [19,21,22,27,40,41], and is insofar critical as gloves are often not worn in areas where no contamination is expected [42]. Nevertheless, the present findings generally range in lower magnitudes than results from older studies [13,33,43,44] and also from more recent international studies [19,28,31,41,[45][46][47], indicating country-specific levels of contamination and pointing out the constant improvements in occupational hygiene practice in the participating pharmacies. The continuous improvement is likely to have benefitted from repeated and long-term monitoring.…”
Section: Overall Resultssupporting
confidence: 91%
“…Sodium hydroxide 0.03 M has been used for wetting surfaces/wipes and extracting cytotoxic drugs from samples after carrying out environmental monitoring. 7,11,12,19,20 Our study found that paclitaxel in sodium hydroxide 0.03 M degraded within 60 minutes. This has also been reported by the World Intellectual Property Organization and is not recommended as a wetting agent for environmental monitoring of paclitaxel; isopropanol 50% solution should be used instead.…”
Section: Discussionmentioning
confidence: 82%
“…A large body of human evidence supports the use of PPE as exposure of workers to cytotoxic drugs has been a recognised health hazard in facilities where cytotoxic agents are being prepared, stored or handled (Sessink and others 1992, Mc Devitt and others 1993, Mason and others 2005). Cytotoxic residues have also been detected on the exterior of unopened vials and in wards distant from areas where antineoplastic agents were handled, causing concerns for personnel not directly involved in their preparation or administration (Nygren and others 2002, Lee and others 2007, Fleury-Souverain and others 2014, Janssens and others 2015). …”
Section: Discussionmentioning
confidence: 99%